Stereotactic body radiotherapy for spine and non-spine bone metastases in prostate carcinoma: a multicenter cohort analysis - Nägler, Franziska; Seiler, Isabell; Schäfer, Sebastian; Meents, Johannes; Lohaus, Fabian; Grün, Arne; Wittenstein, Olaf; Klischies, Kenneth; Remmele, Julia; Rühle, Alexander; Eckl, Miriam; Blanck, Oliver; et al. (Journal of bone oncology, 2025)
Background and purpose - Metastases-directed radiotherapy plays an increasing role in oligometastatic prostate cancers (OMPC). Here, we investigated the role of stereotactic body radiotherapy (SBRT) for spine and non-spine bone metastases (BoM) from prostate cancer in a large real-world multicenter cohort. - Material and methods - This multicenter cohort analysis from five tertiary cancer centers included patient data of spine and non-spine BoM irradiated between 2010 and 2024. Overall survival (OS), progression-free survival (PFS), local recurrence-free survival (LRFS), SBRT target volumes and doses, toxicity, and the role of additional systemic therapies were evaluated retrospectively. - Results - 231 patients (341 BoM) with median follow-up time of 28.3 months were included. Most common localization were spine (39.3 %), pelvic bone (31.7 %), and ribs (17.9 %). 1- and 5-year PFS for spine BoM were 93.8 % (95 %CI:84.2-97.6 %) and 32.1 % (95 %CI:16.8-44.4 %) and for non-spine BoM 91.7 % (95 %CI:85.1-95.5 %) and 36.6 % (95 %CI:25.8-47.5 %), respectively. 1- and 5-year OS for spine BoM amounted to 94.2 % (95 %CI:85.3-97.8 %) and 69.2 % (95 %CI:50.2-82.2 %) and for non-spine 100 % and 73.3 % (95 %CI:59.1-83.3 %). Older age (p < 0.005) and additional systemic therapies (p = 0.05) were associated with worse OS, older age and larger treatment volumes with worse PFS (p = 0.04). Toxicities were low, with fracture rates of 0.3 % (acute) and 1.2 % (late). - Conclusion - Bone SBRT for OMPC is an effective treatment with low toxicity and particularly low fracture rates for both spine and non-spine BoM with no difference in outcome based on the localization. Prospective trials will help to identify the patients benefitting most from this approach and to establish standardized SBRT concepts incorporating systemic treatments.